(The Utilization of Tofu Pressed Cake in The Production of High Dietary Fiber Flour as an Alternative of Functional Food Inggredient) - Ahmad Sulaeman; Sulistiani -; Dadang Supriatna (Warta Industri Hasil Pertanian, 2007)
High fiber tofu pressed cake a as by producton manufacturing tofu is posibble to used for raw material on preparing alternative functional food ingredient.This reasearch was designed to study the manufacturing of high fiber flour from tofu pressed cake.The flour flow process chart described as follow.The first flour processed from tofu fresh cake which then dried on drum dryer prior to be milled to become 60 mesh flour.The second one processed from tofu fresh cake which then pressed,sterilized,followed by soaking on sodium metabisulfit 3% for 40 minutes,pressing,freezing,drum drying,and milling to become60 mesh flour.The third one processed from tofu fresh cake which then pressed,sterilized,followed by soaking on sodium metabisulfit 0.1% for 40 minutes,pressing fermentation using neurospora sitophila mould (2,5% for 24 hours),freezing,drum dyring, and milling to become 60 mesh flour.The flour was then analyzed for physico chemical,functional and sencory properties.Soaking in sodium metabisulfit 3% for 40 minutes before drying increase whiteness of flour.Fermentation with neurospora sitophila improve protein digesbility but lower the whitenes.Soaking in sulfit and fermentation increased the flour solubility dietary fiber and descreased unsoluble dietary fiber.The fiber total content in the flour ranged from 46.75 up to 56.24% (db)and the consumption of 25 g of the flour will contribute 50% of the fiber RDA (Recognice Daily Allowance).